A revision of the French Telothelepodidae and Thelepodidae (Annelida, Terebelliformia), with descriptions of three species and first European record of a non-indigenous species - Lavesque, Nicolas; Londoño-Mesa, Mario H.; Daffe, Guillemine; Hutchings, Pat (Zootaxa, 2020)
Telothelepodidae and Thelepodidae from French waters are revised based on material available in French marine stations and newly collected specimens. This work is the second part of the Spaghetti Project aiming to revise French species of “Spaghetti” worms. It describes three new species using both morphological and molecular tools: Streblosoma cabiochi n. sp., Streblosoma lindsayae n. sp. and Thelepus corsicanus n. sp. This study also permitted us to detect the presence of an Asiatic species, Thelepus japonicus, in Arcachon Bay and Normandy, introduced via oysters transfers. An identification key for European species of both families is also provided.